Reynolds number dependence of near field vortex motion downstream from an asymmetrical nozzle - Van Hirtum, A.; Grandchamp, X.; Cisonni, Julien (2012)
Smoke visualisation is used to quantify the influence of low to moderate Reynolds number (<1100) on near field vortex motion downstream from an asymmetrical nozzle. The influence of Reynolds number is found to be predominant for low Reynolds numbers (<500). The relationship between Reynolds number and vortex shedding is assessed.